INDIVIDUAL WORK OF STUDENTS IN THE INFORMATION EDUCATIONAL ENVIRONMENT - Чичерская, Маргарита; Гончарук, Людмила; Бруневич, Инесса; Маковийчук, Кристина; Поддубная, Антонина (SWorldJournal, 2021)
Abstract: Practical modes to organization and realization of individual work of students in conditions of information educational surroundings in the process of preparing of specialist of medical sphere are found out in the article. Individual work of stu